A representação social do fenômeno participativo em organizações publicas do Rio de Janeiro - Moller, Renato Cesar (1996)
The theory of social representation underlines this paper. It is based on the results of empirical research associated with a selected sample of civil servants. It aims at outlining the communication area through which the location for participation in the context of public administration of the state is defined. In the theoretical realm, the relation between social representation and behavior is highlighted, with major emphasis on the analysis of structural properties of the representation, through the identification of its core and of its associated peripheric systems as well. The results show that, far from estimulating corporative practices, the use of participative management forms may contribute to the construction of a public administration model wich acomplishes the requirements of efficiency, efficacy and effetiveness.